Implementasi Kebijakan Manajemen Sumber Daya Insani dalam Meningkatkan Kinerja Orgnanisasi Sekolah di MI Ma’arif Sentul Tanggulangin Sidoarjo - Amalia Fatkhan, Regita; Yusron Maulana El-Yunusi, Muhammad (Institut Agama Islam YPBWI Surabaya, 2024)
The purpose of this study is to document and showcase the ways in which MI Ma'arif Sentul Tanggulangin Sidoarjo's school organizations have benefited from human resource management strategies by enhancing their performance in areas such as planning, recruiting, and selection. Observation and interviews are the main methods of data gathering in this qualitative study. Human resource management at MI Ma'arif Sentul is carried out by the head of the department through annual supervision evaluations and the implementation of HR planning programs pertaining to policies for recruiting honorary staff, according to the research. The effectiveness of school organizations is greatly enhanced by schools, which offer salaries and transfers f or personnel.